Participative mechanisms to improve office maintenance performance and customer satisfaction / Cheong Peng Au-Yong, Azlan Shah Ali and Faizah Ahmad - Au-Yong, C.P.; Ali, A.S.; Ahmad, F. (ASCE, 2015)
Buildings can be poorly maintained due to lack of understanding towards the role of building maintenance in achieving organisation's objective and long-term profitability. The maintenance management is the agent that provides maintenance services to fulfil the needs of the organisation. However, involvement of all the key participants is the key to enhance maintenance planning, execution, and outcome. Whereby, participative mechanism involves the key participants to deal with the maintenance issues. Thus, this paper seeks to identify the participative mechanisms through literature review; then, establish relationship between the mechanisms and maintenance performance through questionnaire survey and interview; and finally produce a regression model for prediction purpose. The findings reveal that effective communication among the key participants is vital to enhance the maintenance performance. Therefore, this paper recommends that the management should develop an effective communication platform involving all key participants with contribution and commitment toward the maintenance activities.